2020
DOI: 10.3390/antibiotics9090630
|View full text |Cite
|
Sign up to set email alerts
|

Current Antibiotic Resistance Trends of Uropathogens in Central Europe: Survey from a Tertiary Hospital Urology Department 2011–2019

Abstract: Monitoring of pathogen resistance profiles is necessary to guide empirical antibiotic therapy before culture and sensitivity results become available. The aim of this study was to describe current antibiotic resistance patterns of five most frequent causative uropathogens in a Department of Urology of a tertiary referral centre in Central Europe over a period of nine years. The Hospital Department of Clinical Microbiology database was used to extract data on all positive urine samples from inpatients in the De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 45 publications
9
50
2
Order By: Relevance
“…In this study, the second frequently isolated bacteria were K. pneumoniae rods (13.7%), which is in accordance with the results reported by other authors [ 17 , 18 , 23 ]. In our study, E. faecalis (9.3%) and E. faecium (6.2%) were less commonly isolated from positive urinary cultures, similarly as reported by Mahony [ 21 ], Hrbacek [ 24 ], and Woldemariam [ 20 ]. Our study showed that E. coli was significantly more often isolated from women.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the second frequently isolated bacteria were K. pneumoniae rods (13.7%), which is in accordance with the results reported by other authors [ 17 , 18 , 23 ]. In our study, E. faecalis (9.3%) and E. faecium (6.2%) were less commonly isolated from positive urinary cultures, similarly as reported by Mahony [ 21 ], Hrbacek [ 24 ], and Woldemariam [ 20 ]. Our study showed that E. coli was significantly more often isolated from women.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, 26.2% of E. coli isolates were ESBL producers, about six times more than in previous studies (4.4%) of uropathogenic E. coli isolates (2007–2008) from the same hospital [ 45 ]. Hrbacek et al [ 24 ] showed that between 2011 and 2019 in a Department of Urology of tertiary referral centers in Central Europe, 8.7% of E. coli strains produced ESBL. In the USA in 2017, prevalence of ESBL phenotypes of E. coli was 15.7%, and ESBL isolates showed co-resistance to many oral agents [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our previous related work [ 25 ], urinary cultures from the Department of Clinical Microbiology electronic database between January 2011 and December 2019 were searched for those caused by the following genera: Acinetobacter , Citrobacter , Enterobacter , Morganella , Providencia , Serratia and Stenotrophomonas . Urine cultures may have originated from spontaneously voided midstream samples, aseptic catheterisation during theatre procedures, indwelling catheters, suprapubic catheters, nephrostomy tubes and uretero-ileostomies.…”
Section: Methodsmentioning
confidence: 99%
“…The method used for culture and susceptibility testing has been described elsewhere [ 25 ]. Briefly, uncentrifuged urine was inoculated with a 0.01 ml loop on blood and UriSelect chromogenic agar (Bio-Rad, Berkeley, CA, USA) in a semi-quantitative dilution method.…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli is the most dominant pathogen causing urinary tract infections [ 19 , 20 , 21 ] as well as foodborne illnesses [ 22 , 23 , 24 ], while Staphylococcus aureus is the most common cause for foodborne [ 25 , 26 ], skin and soft tissue infectious diseases [ 27 , 28 , 29 ]. However, over the past decade, the changing pattern of resistance in E. coli and S. aureus has emphasized the need for new antimicrobial agents [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%